Accession games: A dynamic per-member partition function approach - László A. Kóczy (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2000)
In this paper we define and solve the accession game, a dynamic game containing a union and a set of applicants with a per-member partition function satisfying the conditions of Yi [17] to include negative externalities. The solution gives an equilibrium partition of the players as well as, after Morelli and Penelle [12], the optimal path, a subgame-perfect sequence of partitions, where each player maximises the present value of its payoffs subject to others' moves. While this game can be applied in general our motivation was to model the ongoing extensions of the European Union.
Keywords: 330; Dynamic Computable General Equilibrium Model